Enhancing thermal and mechanical response of aluminum using nanolength scale TiC ceramic reinforcement. Issue 8 (1st June 2018) - Reddy, M. Penchal; Himyan, M.A.; Ubaid, F.; Shakoor, R.A.; Vyasaraj, M.; Gururaj, P.; Yusuf, M.; Mohamed, A.M.A.; Gupta, M.
Abstract: In the present work, nano-sized titanium carbide (0.5, 1.0 and 1.5 vol%) reinforced aluminum (Al) metal matrix composites were synthesized by powder metallurgy incorporating microwave sintering and hot extrusion. Microstructural, mechanical and thermal properties of hot extruded unreinforced aluminum and titanium carbide (TiC) reinforced aluminum composites are presented in this paper. X-ray diffraction (XRD) patterns and scanning electron microcopy (SEM) images show the homogeneous distribution of TiC nanoparticles in the Al matrix. The tensile and compressive strengths of Al composites increased with the increase in TiC content, while the ductility decreased. The CTE of Al composite decreased with the progressive addition of hard TiC nanoparticles. Overall, hot extruded Al 1.5 vol% TiC nanocomposite exhibited the best combination of tensile, compressive, hardness and Young's modulus of 186 ± 3 MPa, 416 ± 4 MPa, 9.75 ± 0.5 GPa and ~103 GPa, respectively. High tensile strength and good thermal stability exhibited by Al-TiC nanocomposites developed in this study show the potential for a variety of weight-critical engineering applications.